Mechanical and Durability Properties of Carbonated Recycled Aggregate Concrete - Singh, Harsimranjit (My University, 2018)
Concrete has been proved very commonly used and a leading construction material all around the world for a period of more than a century due to its durability, satisfactory compressive strength, versatility, availability and cost-effectiveness. Around the world, the concrete industry is using the large amounts of natural resources, as a result of this, they are now becoming insufficient to fulfil the increasing demands of industry. Also, the utility of old structures is decreasing, so these structures are demolished to make a way for modern construction. Concrete wastes can be used for making RCA’s after the process of crushing and sieving. These aggregates can be obtained from many sources like demolition waste, construction waste & industrial waste etc. Also, the mechanical & durability properties of the recycled aggregate concrete are weaker than that of normal concrete, due to the mortar attached having a large number of pores or the cracks that form during crushing. Hence, if the attached cement mortar can be improved, then it will increase the applications of RCA. The various methods that can be used to improve the quality of recycled concrete aggregate include mechanical grinding, heat & rubbing method, pre-soaking in acid, two-stage mixing approach, self-healing, ultrasonic cleaning, mineral admixture solution and carbonation method. Therefore, the main objective of this thesis is to improve the quality of recycled concrete aggregates (coarse) by using the “Carbonation” technique and after making the concrete by using these treated aggregates, the Non-destructive, Mechanical and Durability properties of normal concrete, recycled aggregate concrete and carbonated recycled aggregate concrete are compared. A total of three mix combinations named NAC (using 100% natural coarse aggregate), RAC (using 100% recycled coarse aggregate) and CRAC (using 100% carbonated recycled coarse aggregate) were prepared using w/c ratio of 0.48. It has been found that by using the carbonated recycled concrete aggregates (CRCA), RAC’s non-destructive, mechanical and durability properties can be improved because the method of carbonation not only refine the RCA’s properties, also it reduces the greenhouse effect which is originated by CO2 emission. Also, this method used is lower in cost and more environment-friendly than other methods. Due to carbonation of recycled concrete aggregates (RCAs), there is an improvement shown in non-destructive properties like an ultrasonic pulse velocity, rebound hammer; in mechanical properties like an increase in compressive strength, flexural strength, split tensile strength and in durability properties like a decrease in rapid chloride permeability, water absorption, water permeability, sorptivity.
Keywords: CARBONATED RECYCLED AGGREGATE CONCRETE; NATURAL COARSE AGGREGATE; RECYCLED COARSE AGGREGATE; MECHANICAL PROPERTY; DURABILITY PROPERTY